The Importance Of A Healthy Lifestyle In Maintaining The Health Of The Population (Eurasian Research Bulletin, 2023)
The life and health of every person is the greatest social wealth of society. In this family, the school puts the issue of forming a healthy lifestyle in front of the places dealing with human education and development. Everyone's health is naturally determined by a healthy lifestyle.